Settlement of road embankment on prefabricated vertical drain treated soft ground - Abdul Razak Ali, 1967-; Nurly Gofar, supervisor; Fakulti Kejuruteraan Awam (2009)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2009